2013
DOI: 10.1002/eco.1414
|View full text |Cite
|
Sign up to set email alerts
|

Ecohydraulics: linkages between hydraulics, morphodynamics and ecological processes in rivers

Abstract: The articles in this issue are a selection of the 15 main presentations made at the EUROMECH Colloquium 523 'Ecohydraulics: linkages between hydraulics, morphodynamics and ecological processes in rivers' that was organized in Clermont-Ferrand, France, from 15 to 17 June 2011. The Colloquium was attended by 51 participants from 15 countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These forms of technical interference are performed mainly to protect a valley from flood and drought. However, such works can lead to changes in the hydraulic characteristics of a river [5]. Their consequences can interfere with the existing dynamic balance in the stream and surrounding environment, resulting in numerous environmental threats [6].…”
mentioning
confidence: 99%
“…These forms of technical interference are performed mainly to protect a valley from flood and drought. However, such works can lead to changes in the hydraulic characteristics of a river [5]. Their consequences can interfere with the existing dynamic balance in the stream and surrounding environment, resulting in numerous environmental threats [6].…”
mentioning
confidence: 99%
“…The result of these efforts is found in the growing number of publications (see overview in Hannah et al 2004 and, published books (Acreman 2001;Wood et al 2008;Maddock et al 2013 Perception of ecohydraulics, ecohydrology and hydroecology by both practitioners and researchers familiar with these fields, and people outside of these fields displays an overall sense of confusion (Naiman et al 2006;Wood et al 2008;Rickwood et al 2010). Some of the grounds for confusion include the separate disciplinary origins of ecohydrology and ecohydraulics (natural sciences versus engineering, respectively), the scope of the disciplines (incorporation of terrestrial ecosystems vs sole focus on aquatic ecosystems), and the scale of focus (catchment versus micro/mesoscale), the latter for which there is more agreement (Rice et al 2010;Blanckaert et al 2013;Zalewski 2015;Nestler et al 2016b). As an example, Rice et al (2010) found that the theme "ecohydraulics" appealed more to physical scientists than to biologists and ecologists.…”
Section: Introductionmentioning
confidence: 99%